Content analysis of cybercrime infographic - Ahmad, Zeti Azreen; Mubin, Nadia; Arzeman, Akmal (UKM, 2023)
Malaysia is one of the vulnerable regions of cyberattack in which cybercrimes continue to increase at alarming rate. Cyber criminals are attacking not only organisations but also individuals. Various types of cybercrimes that have resulted in significant financial losses have been reported in the media. Despite the daily coverage of cybercrime incidents, people continue to fall victims. Keeping the public informed of the potential online threats should not be taken for granted. This study argues that effective communication of cybersecurity information is essential to enhance public’s resilience in dealing with cybercrimes. Infographic is a useful tool for conveying cybersecurity information. Infographic is a visual communication that is often used to communicate complex messages that include science related information. Literature on infographics often emphasizes on its key components that include; visual, content and knowledge. As a visual form of communication, it makes information appear to be appealing and easier to understand to diverse types of public. The format could be easily shared with others through different types of social media platforms. This study examined infographics related to cybercrimes from CyberSecurity Malaysia’s Facebook account. Visual content analysis has been adopted to analyse more than 20 infographics based on content, visual and knowledge. The study found the content of infographics was mainly text and graphic with instructive guidelines. However, the visual elements appear cluttered, potentially compromising the efficacy of the conveyed message.